POTENSI WISATA ALAM DI KAWASAN AIR TERJUN SALUPONI DESA PANDERE KECAMATAN GUMBASA KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Akbar, Muh.; Rukmi, Rukmi (Jurnal Warta Rimba, 2021)
Saluponi Waterfall is one of the natural tourism potentials which is located in Pandere Village, Gumbasa District, Sigi Regency, Central Sulawesi Province. The potential’s natural tourism of saluponi waterfall's has not been structured adequately and noticed by government properly, but it has been able to attract tourists’ interest by its own allure. Hence, it is necessary to conduct research to find out the potential of natural tourism in the Saluponi Waterfall at Pandere Village, Gumbasa District, Sigi Regency of Central Sulawesi Province. This research was conducted in March to April 2019. In this research, the researcher used descriptive qualitative research design. The field research precisely result of observation, interviews and also documentation of whether the level of the research is feasible or unfeasible of the potential of natural tourism in the Saluponi Waterfall Region is 79.66% with the 3 highest criteria and 1 lowest criteria namely supporting facilities and infrastructure criteria 100.5%, accessibility criteria 109 , 3% and the attractiveness criteria 75.51% while for the lowest criteria is the accommodation criteria 33.33%.Keywords: Waterfall, Attractiveness, Accessibility, Accommodation